Cranial ultrasonographic screening findings among healthy neonates and their association with neurodevelopmental outcomes - Yi-Jie Lin; Nan-Chang Chiu; Hui-Ju Chen; Jia-Yun Huang; Che-Sheng Ho (Elsevier, 2021)
Background: To analyze the findings of cranial ultrasonographic screening in asymptomatic neonates and to assess the association between abnormal results and neurodevelopment. Methods: We retrospectively reviewed the cranial ultrasonographic screening results of healthy neonates born between 35 and 42 weeks gestation at our hospital from October 2011 to October 2018. Results: In total, 11,681 neonates underwent cranial ultrasonographic screening during the study period, and 9666 (82.7%) had normal results. Of 2015 neonates with abnormal findings, 294 had more than two abnormalities. The most common minor findings were subependymal cysts (8.99%), choroid plexus cysts (2.43%), lenticulostriate vasculopathy (2.34%), frontal horn cysts (1.80%), and enlarged cisterna magna (1.04%). Then, 33 (0.28%) neonates had major abnormalities, including cerebral hemorrhage, periventricular heterotopia, focal cortical dysplasia, anomalies of the corpus callosum, and vascular malformation. Of 1334 neonates who underwent serial clinical evaluations, 76 (5.69%) had neurodevelopmental disorders, including developmental delay, attention-deficit/hyperactivity disorder, and autistic spectrum disorder. Conclusion: The incidence rate of intracranial anomalies in healthy neonates was 17.3%, and about 5.69% had neurodevelopmental disorders. Cranial ultrasonographic screening has its own value in helping early detection of intracranial anomalies in healthy neonates, some of which have prognostic implications.